Miskonsepsi Siswa dalam Pembelajaran Online Ilmu Pendidikan Sosial di Satuan Pendidikan Tingkat Pertama - Dian Eka Indriani (Graduate School of Universitas Negeri Malang, 2021)
Abstract: This article describes the understanding of students' concepts, especially the misconceptions that occur during the implementation of online learning for Social Education subjects during the Covid-19 Pandemic throughout the year 2020/2021. The method used is a quantitative approach with the type of survey research. The subjects studied were selected based on convenient sampling, namely class IX students of SMP 1 Negeri Kamal who used the Quizizz application. Data collection techniques using a questionnaire. Data analysis used the Certainty of Response Index (CRI) by matching the score and the accuracy of the answers, after obtaining the score, it could be matched to the table of certainty levels on the CRI scale. The results showed that there was a 50% remediation of student misconceptions.Abstrak: Artikel ini memaparkan pemahaman konsep siswa khususnya miskonsepsi yang terjadi selama pelaksanaan pembelajaran daring mata pelajaran Ilmu Pendidikan Sosial di dalam masa Pandemi Covid-19 sepanjang tahun 2020/2021. Metode yang digunakan adalah pendekatan kuantitatif dengan jenis penelitian survey. Subjek yang diteliti dipilih berdasarkan convenient sampling yakni siswa kelas IX SMP 1 Negeri Kamal yang menggunakan applikasi Quizizz. Tehnik pengumpulan data menggunakan angket. Analisis data menggunakan Certainly of Respone Index (CRI) dengan cara mencocokkan skor dan akurasi jawaban, setelah diperoleh skor, dapat dicocokkan pada tabel tingkat kepastian dalam skala CRI. Hasil penelitian menunjukkan adanya remediasi Miskonsepsi Siswa sebesar 50%.